2013
DOI: 10.1038/bjc.2013.307
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of TGF-β and EGF pathway gene expression and migration of oral carcinoma cells by mucosa-associated lymphoid tissue 1

Abstract: Background:Expression of mucosa-associated lymphoid tissue 1 (MALT1) is inactivated in oral carcinoma patients with worse prognosis. However, the role in carcinoma progression is unknown. Unveiling genes under the control of MALT1 is necessary to understand the pathology of carcinomas.Methods:Gene data set differentially transcribed in MALT1-stably expressing and -marginally expressing oral carcinoma cells was profiled by the microarray analysis and subjected to the pathway analysis. Migratory abilities of cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…Expression of K5/14 is an independent risk factor for worse prognosis of oral carcinomas (31). Although a molecular mechanism for MALT1-dependent keratin alteration is uncertain, our recent microarray analysis indicated that MALT1 preferentially downregulates EGF and TGF-β pathway gene expression (32). EGF and TGF-β signaling suppress K8/18 expression and stimulate K5/14 expression, provoking proliferative and aggressive behavior of carcinoma cells (33)(34)(35)(36)(37).…”
Section: Discussionmentioning
confidence: 94%
“…Expression of K5/14 is an independent risk factor for worse prognosis of oral carcinomas (31). Although a molecular mechanism for MALT1-dependent keratin alteration is uncertain, our recent microarray analysis indicated that MALT1 preferentially downregulates EGF and TGF-β pathway gene expression (32). EGF and TGF-β signaling suppress K8/18 expression and stimulate K5/14 expression, provoking proliferative and aggressive behavior of carcinoma cells (33)(34)(35)(36)(37).…”
Section: Discussionmentioning
confidence: 94%
“…The articles were critically evaluated based on STROBE [Figure 1], and 36 of these were considered for the review. [8910111213141516171819202122232425262728293031323334353637383940414243]…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-one studies focused on genes and the associated pathways that explained the initiation, proliferation, and progression of OSCC. [101114161819202324252627282930313435373943]…”
Section: Resultsmentioning
confidence: 99%
“…Since proteolytic degradation of the extracellular matrix releases growth factors (38), we should consider the impact of carcinoma cell-tissue interactions on the expression carefully. Furthermore, an intracellular signaling molecule, mucosa-associated lymphoid tissue 1, which suppresses the aggressive phenotype of oral carcinoma cells and is inactivated in the patients with worse prognosis directly affects FABP expression (39,40). Therefore both genetic and environmental factors provoke carcinoma cells to express FABP5.…”
Section: Discussionmentioning
confidence: 99%
“…FABP4 transports LCFAs to the nucleus, which is required for stable binding with peroxisome-proliferator-activated receptor (PPAR)-γ. PPAR-γ expression in tongue carcinomas is higher in patients with an improved prognosis (42) and the administration of a PPAR-γ agonist inhibits the development of tongue carcinoma (43). However, oral carcinoma cells showing aggressive phenotypes in vitro strongly upregulate FABP4 expression (40,44). Detailed future studies are required in order to further clarify the role of ectopic expression.…”
Section: Discussionmentioning
confidence: 99%